Carbonate Ramp Facies and Porosity Recognition: Case Study of the Late Albian-Early Cenomanian Mauddud Formation in Ratawi Oilfield, Southern Iraq - Hussain, Salah A.; Ibrahim, Yasamin K. (Iraqi Journal of Science, 2023)
The carbonate ramp facies of the Late Albian-Early Cenomanian Mauddud Formation were studied in the Ratawi Oilfield, Basra Governorate, south of Iraq using integrated borehole data set that included, core and cutting samples in three drilled wells to analyze the petrography of the Mauddud Formation, two hundred and eighty-one (281) thin sections were prepared and examined for the three selected wells. The results show that the formation is composed of light grey dolomitized limestone and pseudo-oolitic creamy limestone with green to bluish shale. The petrographic observations results show four facies’ associations in the Mauddud Formation. These include: Mid–Ramp environment which is represented by Argillaceous mudstone microfacies, Argillaceous wackestone microfacies and orbitolinid wackestone microfacies; the shallow open marine environment which is assimilated by foraminiferal wackestone microfacies and foraminiferal packstone microfacies; a restricted marine environment that represented by bioclastic fossiliferous wackestone microfacies and miliolid wackestone microfacies and Shoal environment is represented by bioclastic packstone microfacies, bioclastic grainstone microfacies, peloidal foraminiferal pack-grainstone microfacies, and peloidal packstone-grainstone microfacies with diverse skeletal grains. The porosity includes Vuggy, Interparticle, Intraparticle and Fracture porosity.